Evolution and demography of the great apes. (December 2016) - Kuhlwilm, Martin; de Manuel, Marc; Nater, Alexander; Greminger, Maja P; Krützen, Michael; Marques-Bonet, Tomas
Abstract : The great apes are the closest living relatives of humans. Chimpanzees and bonobos group together with humans, while gorillas and orangutans are more divergent from humans. Here, we review insights into their evolution pertaining to the topology of species and subspecies and the reconstruction of their demography based on genome-wide variation. These advances have only become possible recently through next-generation sequencing technologies. Given the close relationship to humans, they provide an important evolutionary context for human genetics.